Post-Pandemic University Teaching: Teaching and Evaluation Strategies for Hybrid Learning - Rodríguez-Valerio, Daniela (2025)
Introduction. Education at all levels underwent a transformation after the COVID-19 pandemic, as for approximately two years, educational institutions had to adopt short-term solutions to ensure continuity in teaching and learning processes amidst a health emergency, relying heavily on technology. This reality brought many challenges but also numerous lessons learned—among them, a more widespread adoption of hybrid education models, which continue to this day.Objective. This research focused on identifying teaching and assessment strategies that support meaningful learning among university students in courses delivered in a hybrid format. Methodology. A qualitative, exploratory study was conducted with the participation of 62 university students (43 undergraduate and 19 graduate) enrolled in Library and Information Science programs at the University of Costa Rica. Data were collected through focus groups and analyzed using category construction and triangulation techniques. Results. The study identified characteristics of the learning process that spark students’ interest, as well as teaching and assessment strategies that promote meaningful learning in hybrid courses. Conclusions. Hybrid education is enhanced when in-person sessions are dedicated to practical activities that encourage interaction and participation, while virtual sessions are used to study theoretical content. The study offers practices that can be considered when implementing this educational model.